Digital Libraries during Covid-19 Pandemic: A Bibliometric Analysis and Information Mapping - Pambayun, Kuncoro Galih (Indonesian Journal of Librarianship, 2021)
Problem Statement: Regardless of the significant increase in the use of digital libraries during the Covid-19 pandemic, distribution of its publications has not been mapped as a form of scientific communication. Purpose: Therefore, this research aims to describe and map the information on digital libraries during the pandemic on international publications Scopus indexed. Method: The bibliometric assessment method was used to collect data from 66 publications on the Scopus database. The writer simultaneously used search keywords such as “Digital Library,” “Electronic Library,” and “Covid-19” to determine the publications from January 2020-June 2021. Results: The result showed that 23 (34.8%) out of 66 publications had high relevance to digital libraries during the pandemic, while 74% are scientific journal articles. The country with the largest contribution is the USA, while the largest publisher with only 35% open publications is Emerald. Meanwhile, the central topics in this research map include “Pandemic”, “Covid”, “Library”, and “Services”. Conclusion: The distribution of publications as a form of academic communication has not intertwined, as indicated by the absence of linkage between each author, thereby creating a high potential for studies and publications related to this topic. In addition to increasing the digital literacy of librarians and users, the transformation to high-tech virtual and digital services also stands as an adaptation effort. Keywords: Bibliometric Analysis; Covid-19; Digital Libraries; Electronic Libraries; Pandemic Era